2016
DOI: 10.3389/fmicb.2016.00193
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq Profiling Reveals Novel Target Genes of LexA in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: LexA is a well-established transcriptional repressor of SOS genes induced by DNA damage in Escherichia coli and other bacterial species. However, LexA in the cyanobacterium Synechocystis sp. PCC 6803 has been suggested not to be involved in SOS response. In this study, we performed RNA-seq analysis of the wild-type strain and the lexA-disrupted mutant to obtain the comprehensive view of LexA-regulated genes in Synechocystis. Disruption of lexA positively or negatively affected expression of genes related to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 59 publications
4
50
1
Order By: Relevance
“…The marine cyanobacteria of the genus Prochlorococcus and Synechococcus share a very similar lexA (clade C), while other strains possess a slightly different lexA (clade B), such as A. marina MBIC11017, and both Nostoc PCC7120 and Synechocystis PCC6803 (Li et al, 2010). Interestingly, the Synechocystis PCC6803 lexA gene appeared to regulate carbon assimilation (Domain et al, 2004) and cell motility (Kizawa et al, 2016), but not DNA recombination and repair (Domain et al, 2004). Furthermore, the Nostoc PCC7120 LexA protein has a RecA-independent autoproteolytic cleavage (Kumar et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The marine cyanobacteria of the genus Prochlorococcus and Synechococcus share a very similar lexA (clade C), while other strains possess a slightly different lexA (clade B), such as A. marina MBIC11017, and both Nostoc PCC7120 and Synechocystis PCC6803 (Li et al, 2010). Interestingly, the Synechocystis PCC6803 lexA gene appeared to regulate carbon assimilation (Domain et al, 2004) and cell motility (Kizawa et al, 2016), but not DNA recombination and repair (Domain et al, 2004). Furthermore, the Nostoc PCC7120 LexA protein has a RecA-independent autoproteolytic cleavage (Kumar et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…While ruvB was found to operate in DNA-recombination, lexA appeared to regulate carbon assimilation (Domain et al, 2004) and cell motility (Kizawa et al, 2016) but not DNA repair (Domain et al, 2004). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the transcription of over 500 genes was altered in various functional categories and the transcription of 63 genes altered twofold or more. Global transcriptomic studies have been carried out on Synechocystis using either microarrays or RNA-seq to examine the effects of various conditions (Anfelt, Hallstr€ om, Nielsen, Uhl en, & Hudson, 2013;Hern andez-Prieto et al, 2012;Hihara, Kamei, Kanehisa, Kaplan, & Ikeuchi, 2001;Huang, McCluskey, Ni, & Larossa, 2002;Kizawa, Kawahara, Takimura, Nishiyama, & Hihara, 2016;Kl€ ahn et al, 2015;Kopf et al, 2014;Lau, Foong, Kurihara, Sudesh, & Matsui, 2014;Wang, Postier, & Burnap, 2004;Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%